2019
DOI: 10.1002/ese3.315
|View full text |Cite
|
Sign up to set email alerts
|

Lifecycle energy and greenhouse gas emissions analysis of biomass‐based 2‐ethylhexanol as an alternative transportation fuel

Abstract: This study investigates the environmental performance of 2‐ethylhexanol (2‐EH), as a potential drop‐in transport fuel alternative. Three different biomass‐based production pathways are evaluated and compared using life cycle assessment (LCA) methodology. The environmental impact of 2‐EH is assessed in terms of cumulative energy demand (CED) and global warming potential (GWP). Among the three alternative pathways, 2‐EH produced via syngas results in the lowest primary energy demand and GHG emissions under the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…Bio-based drop-in fuels that have been considered in the Swedish "Future Fuels project" are, e.g., oxymethylene dimethyl ether (OME), n-octanol, 2-methyltetrahydrofuran, 2-ethylhexanol, n-decanol, and 2-propylheptanol. All these can be produced from feedstocks like ligno-cellulose (e.g., from paper pulp production), starch, sugar, oil from plants, or as electrofuels [16].…”
Section: Different System Perspectivesmentioning
confidence: 99%
“…Bio-based drop-in fuels that have been considered in the Swedish "Future Fuels project" are, e.g., oxymethylene dimethyl ether (OME), n-octanol, 2-methyltetrahydrofuran, 2-ethylhexanol, n-decanol, and 2-propylheptanol. All these can be produced from feedstocks like ligno-cellulose (e.g., from paper pulp production), starch, sugar, oil from plants, or as electrofuels [16].…”
Section: Different System Perspectivesmentioning
confidence: 99%
“…The transportation sector is one of the main energy sectors in the world 1,2 . A significant share (approximately 28%) of the world's energy consumption belongs to the transportation sector 3 .…”
Section: Introductionmentioning
confidence: 99%
“…38−43 A recent life cycle assessment of the three bio-routes indicated that 2-ethylhexanol produced via syngas leads to the lowest energy demand and greenhouse gas emissions. 44 Fumaric acid is one of the top 12 bio-based building-block chemicals and its biological synthesis has been extensively investigated. 45,46 For example, Huang et al disclosed that fumaric acid can be obtained in 44% yield from the raw material cornstarch using modified Rhizopus oryzae as the producer.…”
Section: ■ Introductionmentioning
confidence: 99%